HR analytics: The onto‐epistemology and politics of metricised HRM. (3rd February 2020) - Greasley, Kay; Thomas, Pete
Abstract: The development of HR analytics, the growing dominance of positivistic approaches in academic HRM, and the increasing influence of evidence‐based approaches on HR represent a convergence of contextual factors that have the potential to influence HR practice significantly. In this context, we examine how the HR analytics "project" may unfold base on a reflective analysis of a number of data‐rich well‐being projects and empirical evaluations. We focus on the ways in which participants may become enrolled and mobilised in such projects and the implications this has for perceived value and effects of "data" generated by HR analytics. In particular, we draw attention to the social, political, and onto‐epistemological processes of the analytics project and draw conclusions about the way in which the analytics project may influence professional practice.